2019
DOI: 10.1183/13993003.00295-2019
|View full text |Cite
|
Sign up to set email alerts
|

Circulating adhesion molecules and subclinical interstitial lung disease: the Multi-Ethnic Study of Atherosclerosis

Abstract: Adhesion molecules may contribute to the development of interstitial lung disease (ILD) and have been proposed as prognostic biomarkers in idiopathic pulmonary fibrosis. Our objective was to determine whether the circulating adhesion molecules soluble intracellular adhesion molecule (sICAM)-1, soluble vascular cell adhesion molecule (sVCAM)-1 and P-selectin are associated with subclinical ILD in community-dwelling adults.The Multi-Ethnic Study of Atherosclerosis enrolled males and females aged 45–84 years from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 41 publications
2
18
0
Order By: Relevance
“…First, we found that VCAM-1 serum levels were increased in patients with RA-ILD + in relation to those with RA-ILDand IPF. In this context, it has been described that VCAM-1 is induced by both inflammatory cytokines and hypoxia (Peter et al, 1999;Dessein et al, 2005;Navarro-Hernández et al, 2009;Cook-Mills et al, 2011;Murdaca et al, 2012;Wang et al, Frontiers in Molecular Biosciences frontiersin.org 2015; Kong et al, 2018;McGroder et al, 2019), which may explain the increase of this protein observed in our RA-ILD + patients. Likewise, its ability to stimulate the fibroblast proliferation may be related to the fibrotic properties of this disease (Agassandian et al, 2015;McGroder et al, 2019).…”
Section: Discussionmentioning
confidence: 53%
“…First, we found that VCAM-1 serum levels were increased in patients with RA-ILD + in relation to those with RA-ILDand IPF. In this context, it has been described that VCAM-1 is induced by both inflammatory cytokines and hypoxia (Peter et al, 1999;Dessein et al, 2005;Navarro-Hernández et al, 2009;Cook-Mills et al, 2011;Murdaca et al, 2012;Wang et al, Frontiers in Molecular Biosciences frontiersin.org 2015; Kong et al, 2018;McGroder et al, 2019), which may explain the increase of this protein observed in our RA-ILD + patients. Likewise, its ability to stimulate the fibroblast proliferation may be related to the fibrotic properties of this disease (Agassandian et al, 2015;McGroder et al, 2019).…”
Section: Discussionmentioning
confidence: 53%
“…In addition, among familial interstitial pneumonia patients, those with ILA have been found to have shorter telomeres in peripheral blood than those without ILA [ 40 ]. Among other possible biomarkers, the adhesion molecule sICAM-1 has been associated with ILA [ 41 ] as well as pro-inflammatory molecule resistin [ 17 ]. Additionally, leptin and the metabolites phosphatidylcholine, phosphatidic acid, betaine aldehyde, phosphatidylethanolamine, and 1-acylglycerophosphocholine [ 42–44 ] have been linked with ILA and certain microRNAs, in particular miR-193a-5p and miR–502–5p, have been shown to be upregulated in ILA and suggested as ILA biomarkers [ 45 ].…”
Section: Epidemiological Associations and Parallels With Interstitial Lung Diseasementioning
confidence: 99%
“…The MUC5B promoter variant has been associated with interstitial lung abnormalities (ILAs) in both families 132 and population-based cohorts. [133][134][135] Several peripheral blood biomarkers have been associated with early interstitial changes in families 131 or general populationbased cohorts [136][137][138][139] ; however, none of these biomarkers is currently approved or available for clinical use. The role of environmental exposures as a determinant of disease penetrance and phenotype has not been well studied; identifying modifiable risk factors could enable preventive strategies in high-risk individuals.…”
Section: Implications For Relatives Of Fip Patientsmentioning
confidence: 99%